Structural Performance of Authentic Architectural Heritage Designs: a Masonry Monument in Western Anatolia - Demir, H.A.; Aktaş, Engin; Hamamcıoğlu Turan, Mine; Hamamcıoğlu-Turan, M.; Yücetürk, K.; Aktaş, E. (KeAi Communications Co., 2023)
The aim of the study is to present a multi-leveled comparative evaluation approach for structural characteristics of historic masonry monuments so that the consciousness in their authentic designs is comprehended, and the optimum structural performance is clarified. A case study approach is preferred by the examination of the Bedesten (15th‒16th centuries) located in Bergama, İzmir, Turkey. The structure is documented through tacheometric techniques. The construction techniques of structural elements are mapped. These documented qualities are compared with similar period and/or function structures in order to rank the frequency of construction details. The geometrical factor of safety state is defined theoretically for domes and arches. Finite element macro model of the Bedesten is generated in ANSYS software and overall structural analysis of the structure is made to evaluate the safety level of historic building by the limit states through self-weight analysis. The presented study shows that the rare structural characteristics can both contribute to structural safety and cause vulnerability. Therefore, total consciousness in structural design cannot be stated for the studied Bedesten, but the structural designs that are often preferred in the monuments built at the same period in the proximity to each other have low vulnerability, yielding to conscious preferences. © 2023 Higher Education Press Limited Company
Keywords: Architectural heritage; Bergama Bedesten; Construction techniques; Numerical analysis; Structural theory of masonry